Influence of Temperature on the Iron Metabolism of a Fluorescent Pseudomonad - Garibaldi, J. A. (1971)
The iron requirement for maximal cell yields of a fluorescent pseudomonad increases as the temperature of incubation is increased. On a succinate salts medium, maximal cell yields are attained at iron concentrations of 0.10 μg/ml of added iron at 20 C and at 3.0 μg/ml of added iron at 28 C. This bacterium does not grow in the basal medium at 31 C even in the presence of 0.01 to 10 μg/ml of added iron. The inability to grow at the higher temperature is due to the loss, by this organism, of its ability to biosynthesize hydroxamate iron transport compounds at temperatures of 28 C and above, since supplementation with such compounds produced by this organism at lower temperatures promoted growth at 31 C. The biosynthesis of these compounds at lower temperatures contributes to the efficient utilization of iron by the bacterium.